Analysis of the Differences in VAK Learning Styles and Learning Motivation in Terms of Active and Inactive Organizational Membership - Sriana Septiawati; Julia Aridhona; Lisdayani Lisdayani; Widia Safitri (Jurnal Indonesia Sosial Sains, 2026)
Adolescents often feel pressured to conform to their peers, particularly in terms of physical appearance, behavior, and social values. The current phenomenon of adolescent problems is diverse, encompassing psychological, social, and educational challenges. Education is an activity that is inseparable from the learning process, both inside and outside the classroom. The Student Council (OSIS) serves as a forum for student development aimed at developing students’ interests, talents, and potential holistically. Learning styles are preferred ways of thinking, processing, and understanding information. The root of the educational crisis is ineffective learning. Learning motivation is defined as a change in energy within an individual characterized by the emergence of affective feelings and reactions directed toward achieving goals. This study aims to analyze the differences in learning styles (VAK: visual, auditory, and kinesthetic) and learning motivation in terms of active and inactive organizational membership. The data collection method used was a questionnaire on learning styles (VAK) and learning motivation. Overall, the Spearman correlation coefficient (ρ = 0.284) indicates a weak positive relationship between learning styles and learning motivation. A p-value of 0.002 indicates that this relationship is statistically significant (p < 0.05). This means that, although the relationship is not strong, there is a tendency for certain learning styles, particularly kinesthetic learning, to be associated with higher levels of learning motivation. This finding underscores the importance of learning approaches that support active and enjoyable learning styles in maintaining or enhancing students’ learning motivation.